The relationship between sleep posture and subacromial impingement syndrome - Yatağanbaba, Alper; Deniz, Çağatay; Süslü, Ahmet Emre; Atay, Özgür Ahmet (Acta Medica, 2026)
Objective: Subacromial impingement syndrome is the most common cause of shoulder pain. One of the possible etiological factors of subacromial impingement syndrome is sleep posture. This study, it is aimed to evaluate the relationship between subacromial impingement syndrome and sleep posture. Materials and Methods: This study received approval from the Institutional Clinical Research Ethics Committee. (No: 2021/04-54). It included 71 patients who underwent polysomnography at the Ear-Nose-Throat Sleep Laboratory between February and June 2021, meeting the study’s inclusion and exclusion criteria. Patients were divided into two groups: 34 who met both diagnostic criteria for subacromial impingement syndrome and 37 who did not meet either criterion. The two groups were compared in terms of demographics, sleep postures, and polysomnography results. Additionally, the relationship between lateral decubitus posture and the affected shoulder was examined in the impingement group. Results: No significant differences were found between the groups in terms of demographic data, except for smoking (p=0.006). The subacromial impingiment syndrome group spent significantly more time in the lateral decubitus posture than the control group (p=0.003), and they also spent significantly more of their sleep time in the lateral decubitusposition on the painful shoulder (p<0.001). Furthermore, the control group had a significantly higher number of posture changes during sleep (p=0.002). Conclusion: This study objectively demonstrated the relationship between sleep posture and subacromial impingement syndrome using polysomnography. With this feature, it differs from the limited number of studies that have been done on this subject before. With this study, it has been shown that the lateral decubitus posture during sleeping is a risk factor for subacromial impingement syndrome, and the posture changes during sleep may also be a protective factor for subacromial impingement syndrome.